Enantiocontrolled Connective Synthesis of Allenes by Carbenoid Eliminative Cross-Coupling between α-(Methylthio)vinylcuprate Species and α-(Carbamoyloxy)alkylboronates - Cao, Yang; Blakemore, Paul R. (Synlett, 2023)
A convenient enantiocontrolled synthesis of allenes (R1R2C=C=CHR3, R1 = aryl/alkyl, R2, R3 = alkyl) is described based on carbenoid eliminative cross-coupling (CEXC) between geometrically pure higher-order α-(methylthio)vinylcuprates, generated in situ by carbocupration of thioalkynes (then activation by addition of n-BuLi), and enantioenriched α-(carbamoyloxy)alkylboronates (15 examples, 30–78% yield, 15–95% ee). The stereochemical fidelity of this CEXC process is substrate dependent, a phenomenon tentatively attributed to a putative organocopper-mediated allene racemization pathway.
Keywords: allene; ate complex; carbenoid; double bond; elimination; 1,2-metalate rearrangement